Qualitative analysis of aggressive behaviors in the adolescent, youth and adult soccer World Cups - Shafizadeh, M. (International Journal of Performance Analysis in Sport, 2008)
The purposes of the present investigation were the analysis of aggressive behaviors and their relationship with performance according to the person-context interaction model. All squads that participated in the soccer World Cups for U-17, U-21 and adults were selected. Predictor variables were squad characteristics including players' body mass index, age, number of tournaments participated in, squads' place, and play round, and criterion variables were aggressive behavior as reflected by cards, fouls, and performance. The results of path analysis and MANOVA mixed factorial design revealed that the aggressive behaviors are associated with number of tournaments participated in and play round. In addition, the preliminary performance is related to aggression, but these results didn't show for knock-out performance. In conclusion, the aggressive behavior in the elite level of soccer is related to the interaction of squad characteristics and stress and aggression causes deterioration in the performance.